DLS Associates : The Way Ahead - Sar, Ashok Kumar (Prabandhan: Indian Journal of Management, 2020)
The case was structured around a decision dilemma related to growth faced by the management of DLS Associates. The case traced the origin and history of the firm and the challenges facing the firm after years of superior performance. Various options on growth were explored, such as geographic expansion, expanding services to residential domain, and diversifying to offer other services to commercial establishments. Strategic choices covering winning aspiration – where to play, how to win, required capabilities, and necessary management systems – were discussed. A structured analysis covering structure and size of the market segments, drivers of customer value, required capabilities, relative costs, and competitors’ reaction was done. The data concerning this case study were gathered from interaction with the Chief Executive Officer and the Chief Operating Officer of DLS Associates. Various barriers to the necessary conditions to be true were discussed and tests were conducted for the critical barriers. The test results were expected to give meaningful insights for resolving the decision dilemma.